(untitled) (Journal of Economic Research & Business Administration, 2021)
The importance of keeping company accounts is to promote the growth evaluate the performance of small and medium scale enterprises (SMEs). Many business entities collapse few years after their incorporation due to poor management arising from weak accounting structure. This study, therefore, examines the relationship between company accounts preparation and the financial performance of SMEs in Nigeria. The study adopts a survey research design. The sample size of 380 respondents was drawn from 20 selected SMEs using a purposive sampling technique. Primary data was collected by administering questionnaire to SMEs operators. Multiple Regression model and correlation analysis were employed to analyze the data. The results of data analysis confirm a strong positive relationship between the company accounts preparation and the financial performance of SMEs in Nigeria. This was established from the p-value of 0.00 which is less than 0.01 significant level (0.00 < 0.01). This study concludes that, the adequate company accounts preparation will reflect financial performance of SMEs in Nigeria. This study discovers that some SMEs operators in Nigeria hired unskilled accounting personnel making it difficult for them to prepare reliable annual accounts and reports. This study, therefore, recommends that the SMEs operators in Nigeria should be maintaining proper accounting records of their operations and hire experienced accounting personnel. Findings from this study will gear up the SMEs operators to appreciate the need to adequately prepare reliable company accounts that will reflect the financial performance of their businesses. Key words: Company accounts preparation, financial performance, SMEs.